Workplace Spirituality and Job Outcomes - Explicating the Relationship in Higher Education in Delhi-NCR - Richa Sinha, Anamika Pandey, (European Economic Letters (EEL), 2024)
Management research now includes spirituality as a subject of study. Academy of Management (AoM), established the Journal of Management, Spirituality and Religion (JMSR) interest group in 1999 to acknowledge significance of spirituality in enterprises. Currently, the significance of workplace spirituality is increasing among both academics and corporates. An unpredictable work environment, marked by frequent layoffs & restructuring and advent of new technologies has been the driving force for the increasing adoption of workplace spirituality. Discouraged personnel are seeking spiritual remedies for the ensuing tensions and stress. Confronted with fear, social isolation, and ongoing turbulent transformations, employees are engaged in a personal quest for a more profound understanding of life. For it is work where they devote a substantial portion of their time.